-6b+8+4b=-3b+13

Simple and best practice solution for -6b+8+4b=-3b+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6b+8+4b=-3b+13 equation:


Simplifying
-6b + 8 + 4b = -3b + 13

Reorder the terms:
8 + -6b + 4b = -3b + 13

Combine like terms: -6b + 4b = -2b
8 + -2b = -3b + 13

Reorder the terms:
8 + -2b = 13 + -3b

Solving
8 + -2b = 13 + -3b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '3b' to each side of the equation.
8 + -2b + 3b = 13 + -3b + 3b

Combine like terms: -2b + 3b = 1b
8 + 1b = 13 + -3b + 3b

Combine like terms: -3b + 3b = 0
8 + 1b = 13 + 0
8 + 1b = 13

Add '-8' to each side of the equation.
8 + -8 + 1b = 13 + -8

Combine like terms: 8 + -8 = 0
0 + 1b = 13 + -8
1b = 13 + -8

Combine like terms: 13 + -8 = 5
1b = 5

Divide each side by '1'.
b = 5

Simplifying
b = 5

See similar equations:

| 28=2[(w+2)+w] | | 2x+240=260 | | -3a+5+4a=11-27 | | 15=7w+2/2+3w+5/4 | | 3R=D+5 | | V=9*6*5 | | (x+4)+(2x-1)=24 | | 10y=4y+10+5 | | 4z+20=3z+3 | | C=2*3.14*7.24 | | (x+15)*3/5-7/12=15 | | x+15*3/5-7/12=15 | | 1/2*23*38=A | | 1/2*23*38 | | -6x+40=31-4x | | x^2-14x=4 | | 2x+240=250 | | 169m^2=0 | | 2x+100=110 | | 33t-26=13t-6 | | 2222222222222222x-5=x-9 | | 38s+15=-2s | | 58x^2+86x+65=35 | | 22x-5=x-9 | | 0=-16t^2+89t | | 4=6+y/2 | | 3=3+x/2 | | -22t+72=35 | | -6u-7=-3u+17 | | 4x+9y=96 | | -52s-66+66=105+66 | | 15x=330 |

Equations solver categories